The effect of attentional focus types as the self-talk form on static and dynamic balance in elderly women - Mansoure Mokaberyan; Somayeh NamdarTajari (University of Tehran, 2018)
Aim: One of the issues that have been considered more than before is the issue of aging. An aging is a period that is accompanied by gradual, progressive and spontaneous erosion changes in most physiological devices and functions of the body. One of the widespread problems that occur in the aging process is the loss of balance, increased fluctuations and the risk of falling. Falling down is one of the most common and most serious problems are aging. For this reason, today, many researchers have drawn attention to the various ways in which elderly people develop their balance. Recently, some researchers have found that the use of cognitive strategies such as self-talk can improve the performance of motor tasks. Self-talk, essentially has two main instructional and motivational functions. Motivational self-talk through increased self-confidence and instructional self-talk by enhancing focus on techniques improve their sports performance and learning skills. On the one hand, it is important to increase the effectiveness of the instructions in order to focus on the focus. Wolfe's researches (1998-1992), given the constrained action hypothesis in most sports skills as well as balance skills, suggest that the use of external attention in comparison with internal attention during the skill leads to better performance and learning. Several studies have been conducted on motivational and instructional self-talk about different athletic skills and different skill levels that have led to a variety of outcomes, but few studies have considered the scope of balance. So, the aim of this study was to evaluate the effect of attentional focus types as the self-talk form on static and dynamic balance in elderly women using instructional self-talk focus strategy. Methodology: The present study was a quasi-experimental study with pre-test and post-test. The experimental group included instructional self-talk with internal focus and instructional self-talk with external attention as well as a control group. The population of the study consisted of all elderly women living in the nursing home in Qazvin who 45 people (66.75 ± 5.65 years) were selected according to the inclusion criteria. Inclusion criteria included Lack of movement restrictions, non-fracture in the lower extremities in the past year and the lack of use of neurological drugs. After the pre-test they were randomly assigned to groups. The control group without self-talk, self-talk group with internal focus and self-talk group with external focus practice their balance skills during the five sessions. At the end of the fifth session, the post- test was conducted using static balance (stork) and dynamic balance (timed up and go) tests. In the stork test, the subject must stand on top of his leg, lift the other leg and stick to the knee of the leg, and simultaneously place his hands on the iliac crest of the pelvis. The time that a person could stand open with his eyes was considered as an indicator of his static balance ability. Each subject performed the test three times and the highest time was recorded. The errors that caused the test to be stopped include lifting the hands from iliac crest of the pelvis, detaching the leg from the knee of the foot and any movement on the foot of the reliance.Each subject performed a three-time test of timed up and go, and his best time was recorded. Since the subject was announcing his stand, the timer began to work, and the timer stopped when it hit the subject back with chair. The self-talk group with the instruction of focus of the internal attention, repeated the words "knee and foot" before each loud performance, which meant "bending slightly knees and maintaining the balance on the foot", and the external attention group referred to the term "target and wall" Which meant "looking at the target mounted on the wall.Results: One-way ANOVA, mixed ANOVA and repeated measure ANOVA were used to analyze the data. Data was analyzed using SPSS software version 20. The significance level was considered 0.05. The results showed that both self-talk groups performed significantly better than the control group in static balance.Conclusion: However Self-talk interferences with both types of attentional focus; it was not a significant difference in the dynamic balance of elderly people (P≥0.05). Taking the results into consideration it can be concluded that, self-talk with internal and external focus instructions can be considered as a cognitive strategy to improve the static balance of elderly people.